2019
DOI: 10.1108/mip-07-2018-0257
|View full text |Cite
|
Sign up to set email alerts
|

An emoji-based metric for monitoring consumers’ emotions toward brands on social media

Abstract: Purpose The purpose of this paper is to introduce and test a new emoji-based metric that could be used to monitor consumers’ emotions toward brands on social media. Design/methodology/approach To test this new metric, 720 consumer tweets were retrieved from official Twitter accounts of 18 leading global brands representing 6 product categories/markets. In order to check its validity, the emoji-based metric was correlated with two measures: the percentage of positive emojis from Brandwatch’s (2018) Emoji Repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 35 publications
2
16
0
1
Order By: Relevance
“…Emoji can also be a way of reflecting consumers' emotions, describing user's profiles (Moreno-Sandoval et al, 2018), and especially monitoring the emotions users feel toward products, brands, and services (Rathan et al, 2017, 2018; Phand et al, 2018; Moussa, 2019). It has been found that gender, age and frequency of usage do not affect consumers' ability to describe and distinguish stimuli with emoji (Jaeger et al, 2018b), and certain emojis can help consumers better differentiate product samples (Schouteten et al, 2019).…”
Section: Research Fields Regarding Emojimentioning
confidence: 99%
“…Emoji can also be a way of reflecting consumers' emotions, describing user's profiles (Moreno-Sandoval et al, 2018), and especially monitoring the emotions users feel toward products, brands, and services (Rathan et al, 2017, 2018; Phand et al, 2018; Moussa, 2019). It has been found that gender, age and frequency of usage do not affect consumers' ability to describe and distinguish stimuli with emoji (Jaeger et al, 2018b), and certain emojis can help consumers better differentiate product samples (Schouteten et al, 2019).…”
Section: Research Fields Regarding Emojimentioning
confidence: 99%
“…Beyond verbal rating systems, Moussa’s (2019) study focused on a non-verbal mechanism: the emoji. This author introduced a new emoji-based metric for monitoring consumer emotions toward brands on social media, associated with the American Customer Satisfaction Index (ACSI).…”
Section: Resultsmentioning
confidence: 99%
“…Business communication and personal communication are the most studied subject areas in neuromarketing applied to social networks. Business communication is presented as the main subject of research by Chmiel et al (2011) , de Vries et al (2012) , Teixeira et al (2012) , Cvijikj and Michahelles (2013) , Goh et al (2013) , Hollebeek and Chen (2014) , Hudson et al (2015) , Hudson et al (2016) , Kim et al (2015) , Khan et al (2016) , Marbach et al (2016) , Dessart (2017) , Kim and Yang (2017) , Schultz (2017) , Swani and Milne (2017) , Swani et al (2017) , Xu and Wu (2017) , Rout et al (2018) , Vignal Lambret and Barki (2018) , and Moussa (2019) . Personal communication is analyzed in studies by Mauri et al (2011) , Meshi et al (2013) , Nelson-Field et al (2013) , Brynielsson et al (2014) , Coviello et al (2014) , Tandoc et al (2014) , Carrillo et al (2015) , Ferrara and Yang (2015) , Lin and Utz (2015) , Lee and Hong (2016) , Wang et al (2017) , Fan et al (2018) , Ng and Kozlowski (2018) , Turel et al (2018) , Vermeulen et al (2018) , Barry et al (2019) , Min and Yun (2019) , Nash et al (2019) , Ranganathan and Tzacheva (2019) , and Sion (2019) .…”
Section: Discussionmentioning
confidence: 99%
“…The use of emojis for the SIM of brand love is legitimate for three convincing reasons: The first reason is that emoji characters have the advantage of being familiar to consumers, who increasingly use them as a partial substitute of standard verbal communication in personal and professional communication irrespective of their native language (Leung and Chan, 2017; Moussa, 2019b). The second reason is that emojis are currently being used by international companies like Anheuser-Busch, Coca-Cola, Chevrolet, Disney, Nestlé, and Starbucks in their corporate communication campaigns (Leung and Chan, 2017).…”
Section: Adopting a Visual Rating Scale For Measuring Brand Lovementioning
confidence: 99%